2000
DOI: 10.1002/1097-0096(200011/12)28:9<497::aid-jcu9>3.0.co;2-3
|View full text |Cite
|
Sign up to set email alerts
|

Pneumatosis of the bladder wall associated with necrotizing enterocolitis

Abstract: Increasing use of sonography for imaging the abdomen of neonates has brought greater recognition of its value in diagnosing and monitoring complications of necrotizing enterocolitis. We describe a case in which pneumatosis of the bladder wall was visualized by sonography in a neonate with Down syndrome and necrotizing enterocolitis. © 2000 John Wiley & Sons, Inc. J Clin Ultrasound 28:497–499, 2000.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2006
2006
2007
2007

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 11 publications
0
1
0
Order By: Relevance
“…These findings appear similar to sono- graphic findings previously described with the abnormal presence of air within the intestine or bladder in patients with intestinal or bladder pneumatosis, respectively. [11][12][13][14] Application of the transvaginal transducer directly above the lesion and immediate depiction of the sonographic finding of air within the lesion essentially negate consideration of the previously mentioned wide differential diagnosis, which must be considered with the characteristic radiologic and CT imaging findings of this condition. A systematic English language literature search (PubMed and MEDLINE) between 1966 and 2005 using the search terms "vaginitis," "emphysematosa," "emphysematous," "Gardnerella," "Trichomonas," "ultrasound," "radiology," and "computed tomography," indicated that the sonographic findings associated with emphysematous vaginitis have not been reported previously.…”
Section: Discussionmentioning
confidence: 99%
“…These findings appear similar to sono- graphic findings previously described with the abnormal presence of air within the intestine or bladder in patients with intestinal or bladder pneumatosis, respectively. [11][12][13][14] Application of the transvaginal transducer directly above the lesion and immediate depiction of the sonographic finding of air within the lesion essentially negate consideration of the previously mentioned wide differential diagnosis, which must be considered with the characteristic radiologic and CT imaging findings of this condition. A systematic English language literature search (PubMed and MEDLINE) between 1966 and 2005 using the search terms "vaginitis," "emphysematosa," "emphysematous," "Gardnerella," "Trichomonas," "ultrasound," "radiology," and "computed tomography," indicated that the sonographic findings associated with emphysematous vaginitis have not been reported previously.…”
Section: Discussionmentioning
confidence: 99%